Catalytic Reduction of Oxygen by a Copper Thiosemicarbazone Complex. Issue 48 (12th November 2020) - Straistari, Tatiana; Morozan, Adina; Shova, Sergiu; Réglier, Marius; Orio, Maylis; Artero, Vincent
Abstract : The new copper(II) thiosemicarbazone complex CuL (H2 L = 4‐{bis[4‐( p ‐methoxyphenyl)‐thiosemicarbazone]}‐2, 3‐butane) was synthesized and structurally characterized. Its electrochemical behavior in N, N ‐dimethylformamide (DMF) was examined. This complex proved active for homogeneous oxygen reduction reaction (ORR) in DMF in the presence of organic acids. The activity and selectivity for ORR were found to be dependent on the nature of the proton source (phenol or acetic acid). This study confirms the previously reported free energy linear correlation between selectivity and overpotential requirement [Passard et al., J. Am. Chem. Soc . 2016, 138, 2925–2928] and suggests that additional descriptors are required for a full understanding of the catalytic ORR behaviour. Abstract : Understanding the selectivity of oxygen reduction with non‐noble metal‐based catalysts is a key topic at the interface between biology and fuel cell technology. The study of the homogeneous electrocatalytic reduction of oxygen with a mononuclear copper(II) thiosemicarbazone complex in the presence of various organic acids as proton sources provides new insights on this topic.